O Centro-Oeste como um fato produção de uma identidade mato-grossense na expressão plástica e a legitimidade artística na exposição Brasil/Cuiabá : Pintura Cabocla (1981) - Ramires, Natalia Noemia Carvalho (2022)
This research aims to analyse the formation process of an attempt to build an identity in Mato Grosso from the plastic expression contained in the collective exhibition Brasil/Cuiabá: Pintura Cabocla, in relation to the political division of the state of Mato Grosso. Through textual and iconographic documents, we intend to analyse which representations permeate this attempt to compose a Mato Grosso identity, as well as from which classification criteria is used by art criticism that aim to legitimize the artistic production of the plastic artists present in this exhibition, among them, Humberto Espíndola, Dalva Maria de Barros, João Sebastião, Adir Sodré, Gervane de Paula, Benedito Nunes, Nilson Pimenta and Alcides Pereira dos Santos. We understand at first that the paintings located in Mato Grosso predominate an iconographic repertoire situated in Mato Grosso's space/territory. However, it is from this conception that the imagetic production of the artists from the collective exhibition will be situated and legitimized by art criticism as a configuration rule, in which their works starts to represent something and become part of the composition, reaffirmation, and representation of an identity. Nonetheless, we must analyse what these images show us. In this sense, to develop this research, we sought theoretical contributions from Roger Chartier, Eric Hobsbawm, Peter Burke, Carlo Ginzburg, and Suzana Guimarães. Seeking to understand the asymmetries that permeate this artistic movement, the classificatory impositions which constitute the art practice in Mato Grosso, through the actions of the Museum of Art and Popular Culture (MACP) of the Federal University of Mato Grosso (UFMT).